THE CONTRIBUTIONS OF FACEBOOK IN THE ACADEMIC LIVES OF STUDENTS AT MINDANAO STATE UNIVERSITY – MAGUINDANAO - Pilot, Sari; Abdula, Datuali; Abdula, Datuali; Blah, Sadat (Advances in Social Sciences Research Journal, 2021)
This study covered the contributions of Facebook in the lives of students particularly at Mindanao State University-Maguindanao. The descriptive-qualitative survey design/method of research was used in this study. Respondents of the study are the 200 selected students from the six Colleges/Department of Mindanao State University – Maguindanao which are as follows: College Arts and Sciences (16), College of Education (46), College Public Affairs and Governance (72), College of Forestry and Environmental Studies (4) College of Fisheries (6) and College of Agriculture (56). Purposive sampling was employed by the researcher in this study in getting the 200 students of Mindanao State University – Maguindanao. The statistical tools used in the study are: frequency distribution, weighted mean, and ranking. On the basis of the findings of the study, the contributions of Facebook in the academic lives of the student at Mindanao State University-Maguindanao were often. However, on problems encountered by the respondents it needs to motivate some aspects under the tips to safe online and policy to secure in the use of Facebook by the respondents/students. Keywords: Contributions, Facebook, Academic Lives of Students